Synthesis of 131I Labeled Quercetin through Oxidation Method Using Chloramine-T for Cancer Radiopharmaceuticals - Maula Eka Sriyani; Dian Ayu Utami; Mega Susilo Dwike; Eva Maria Widyasari; Muharram Marzuki; Rizky Juwita Sugiharti; Witri Nuraeni (Indonesian Journal of Chemistry, 2019)
Quercetin is one of the flavonoid groups with antioxidant activity. The objective of this study was to achieve the labeled compound of 131I-quercetin as a radiotracer for diagnosis and cancer therapy with high labeling efficiency and radiochemical purity. The labeling procedure was conducted by the oxidation reaction using chloramine-T. The effect of pH, reaction time, amount of oxidizing agent and ligand were evaluated in this research. Quercetin was successfully labeled with iodine-131 at pH 11 at room temperature for 10 min mixed in 1000 rpm with the amount of quercetin and chloramine-T is 0.4 and 0.3 mg, respectively. The results demonstrated that the ratio of quercetin/Na131I was 2 × 105. The 131I-quercetin labeling efficiency was 92.03 ± 2.20%, and radiochemical purity of 131I-quercetin was 99.34 ± 0.58%. The results showed that 131I-quercetin could be a radiotracer candidate for diagnosis and cancer therapy.